2005
DOI: 10.1111/j.1365-2796.2004.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term treatment with loop diuretics on bone mineral density, calcitropic hormones and bone turnover

Abstract: Abstract. Rejnmark L, Vestergaard P, Heickendorff L, Andreasen F, Mosekilde L (Aarhus University Hospital and Aarhus University, Aarhus, Denmark). Effects of long-term treatment with loop diuretics on bone mineral density, calcitropic hormones and bone turnover. J Intern Med 2005; 257: 176-184.Background. Loop diuretics (LD) are widely used in the treatment of cardiovascular diseases and disorders with fluid accumulation. LD are known to increase renal calcium losses and may thereby affect calcium homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 31 publications
2
43
1
Order By: Relevance
“…From these studies it was suggested that loop diuretics exerts continuous bone loss and increases bone turnover (Rejnmark et al, 2005a,Lim et al, 2008. These negative effects on bone metabolism may be responsible for an inferior implant fixation and thus for the overall increased risk of revision after primary THA in loop diuretic users as reported in our study.…”
Section: Loop Diuretic Usesupporting
confidence: 59%
See 1 more Smart Citation
“…From these studies it was suggested that loop diuretics exerts continuous bone loss and increases bone turnover (Rejnmark et al, 2005a,Lim et al, 2008. These negative effects on bone metabolism may be responsible for an inferior implant fixation and thus for the overall increased risk of revision after primary THA in loop diuretic users as reported in our study.…”
Section: Loop Diuretic Usesupporting
confidence: 59%
“…However, a previous cross sectional study from the same cohort did not find any association between use of loop diuretics and decreased bone mineral density. Furthermore, two other cross sectional studies, showed diverging results concerning the association between loop diuretic use and bone mineral density in healthy elderly women (Ooms et al, 1993, Rejnmark et al, 2005a. Although reports are conflicting, evidence of loop diuretics potential harmful effect on bone remains.…”
Section: Loop Diureticsmentioning
confidence: 99%
“…Adjustment for confounding was slightly different compared with our study. For example, no correction for chronic diseases was performed in that study, on the other hand the use of vitamin D supplements was taken into account (19). Unfortunately, over-the-counter vitamin D use was not available in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Through direct mailings, we invited women, randomly selected from the local background population to participate in clinical studies concerning the effects of diuretics on calcium homeostasis and bone metabolism (12)(13)(14). The data presented are based on the data from baseline measurements.…”
Section: Methodsmentioning
confidence: 99%